THE VALUE OF FAITH AND BENEFITS OF RITE, ON REPLICA OF PHRATHATPHANOM CHAMLONG TOWARDS BUDDHISTS AT HUAI MEK DISTRICT, KALASIN PROVINCE - Kitjasaro (Sangkampa), Phramaha Meechai; Settamano (Hinsilla), Phramaha Setta (Journal of Buddhist Education and Research (JBER), 2022)
This article aims to study the values of beliefs and benefits of rite on replica of Phrathatphanom Chamlong towards buddhists at Huai Mek district, Kalasin province, which found that there are 3 aspects: 1. Belief: believe that this pagoda is sacred, resulting in those who worship with a bright mind. 2. Rituals: There are Buddhist activities on various important days. And there is an annual event to worship the Lord Buddha. 3. Economic aspect: generate income and circular economy in the community.